Strategi Pemasaran dengan Menggunakan Business Model Canvas (BMC) pada Serantau Coffee X Space di Kota Bandung - Putri Ramadhany Atila; Hayun Setiawan (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
The development of business in Indonesia is experiencing a rapid increase, as can be seen from the many developments of small businesses that are already large, both online and offline, this encourages the creation of increasing competition. Therefore, every business person must determine the effective and efficient marketing of products and services, in order to achieve their business goals. The method used to review marketing strategies using the Business Model Canvas (BMC) at Serantau Coffee x Space in Bandung City is a qualitative method. Based on the results of this study (1) the marketing strategy using the canvas business model runs optimally in attracting consumers and increasing sales turnover. (2) The advantages of the canvas business model are easy to use, have simple visuals, are attractive, flexible, collaborative, and more focused. (3) The lack of a canvas business model is that not all types of business are suitable, especially for businesses that are complex, more unique, innovative, and require effort to create. This may not be suitable for businesses that are in a hurry or have a limited budget.